2020
DOI: 10.1073/pnas.2000278117
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in NRF2 antioxidant pathway regulates winter depression-like behavior

Abstract: Seasonal changes in the environment lead to depression-like behaviors in humans and animals. The underlying mechanisms, however, are unknown. We observed decreased sociability and increased anxiety-like behavior in medaka fish exposed to winter-like conditions. Whole brain metabolomic analysis revealed seasonal changes in 68 metabolites, including neurotransmitters and antioxidants associated with depression. Transcriptome analysis identified 3,306 differentially expressed transcripts, including inflammatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…It is very likely that animals across multiple taxa, including human lineages, exhibit similar seasonality in physiology and behaviors, such as retinal sensitivity and winter depression. In addition, the underlying molecular basis could also be shared among various species, as exemplified by the aforementioned TSH–TH signal transduction machinery associated with seasonal reproduction and the involvement of NRF2 antioxidant pathway in winter depression in both medaka ( 67 ) and humans ( 82 ). Despite the substantial differences between humans and other vertebrates, many biological functions are conserved, making animal models invaluable tools for the scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is very likely that animals across multiple taxa, including human lineages, exhibit similar seasonality in physiology and behaviors, such as retinal sensitivity and winter depression. In addition, the underlying molecular basis could also be shared among various species, as exemplified by the aforementioned TSH–TH signal transduction machinery associated with seasonal reproduction and the involvement of NRF2 antioxidant pathway in winter depression in both medaka ( 67 ) and humans ( 82 ). Despite the substantial differences between humans and other vertebrates, many biological functions are conserved, making animal models invaluable tools for the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses revealed seasonal changes in multiple metabolites (eg, serotonin and glutamate), gene expression (eg, circadian clock genes), and signaling pathways (eg, glucocorticoid receptor signaling and estrogen receptor signaling) previously implicated in depression ( Fig. 2 ) ( 67 ). To further understand the underlying mechanism of winter depression–like behavior, Nakayama et al employed a chemical genomics approach to screen an existing drug library and identified a NRF2 pathway–activating drug, celastrol, that alleviated the social withdrawal of winter medaka.…”
Section: Winter Depression–like Behavior In Medakamentioning
confidence: 97%
See 3 more Smart Citations